Driven electronic bridge processes via defect states in Th 229 -doped crystals - Nickerson, Brenden S.; Pimon, Martin; Bilous, Pavlo; Gugler, Johannes; Kazakov, Georgy A.; Sikorsky, Tomas; Beeks, Kjeld; Grueneis, Andreas; Schumm, Thorsten; Pálffy, Adriana (Physical Review A, 2021)
The electronic defect states resulting from doping Th229 in CaF2 offer a unique opportunity to excite the nuclear isomeric state Th229m at approximately 8 eV via electronic bridge mechanisms. We consider bridge schemes involving stimulated emission and absorption using an optical laser. The role of different multipole contributions, both for the emitted or absorbed photon and nuclear transition, to the total bridge rates are investigated theoretically. We show that the electric dipole component is dominant for the electronic bridge photon. In contradistinction, the electric quadrupole channel of the Th229 isomeric transition plays the dominant role for the bridge processes presented. The driven bridge rates are discussed in the context of background signals in the crystal environment and of implementation methods. We show that inverse electronic bridge processes quenching the isomeric state population can improve the performance of a solid-state nuclear clock based on Th229m.
CRIS-Team Scopus Importer:2021-06-11

Expanding Nuclear Physics Horizons with the Gamma Factory - Budker, Dmitry; Berengut, Julian C.; Flambaum, Victor V.; Gorchtein, Mikhail; Jin, Junlan; Karbstein, Felix; Krasny, Mieczyslaw Witold; Litvinov, Yuri A.; Pálffy, Adriana; Pascalutsa, Vladimir; Petrenko, Alexey; Surzhykov, Andrey; et al. (Annalen Der Physik, 2022)
The Gamma Factory (GF) is an ambitious proposal, currently explored within the CERN Physics Beyond Colliders program, for a source of photons with energies up to approximate to 400 MeV and photon fluxes (up to approximate to 10(17) photons s(-1)) exceeding those of the currently available gamma sources by orders of magnitude. The high-energy (secondary) photons are produced via resonant scattering of the primary laser photons by highly relativistic partially-stripped ions circulating in the accelerator. The secondary photons are emitted in a narrow cone and the energy of the beam can be monochromatized, down to 10(-3)-10(-6) level, via collimation, at the expense of the photon flux. This paper surveys the new opportunities that may be afforded by the GF in nuclear physics and related fields.
CRIS-Team WoS Importer:2022-03-11

Laser-nucleus interactions in the sudden regime - Kobzak, Sergei; Weidenmüller, Hans A.; Pálffy, Adriana (Physical Review C - Nuclear Physics, 2021)
The interaction between medium-weight nuclei and a strong zeptosecond laser pulse of MeV photons is investigated theoretically. Multiple absorption of photons competes with nuclear equilibration. We investigate the sudden regime. Here the rate of photon absorption is so strong that there is no time for the nucleus to fully equilibrate after each photon absorption process. We follow the temporal evolution of the system in terms of a set of rate equations. These account for dipole absorption and induced dipole emission, equilibration (modeled in terms of particle-hole states coupled by the residual nuclear interaction), and neutron decay (populating a chain of proton-rich nuclei). Our results are compared with earlier work addressing the adiabatic regime where equilibration is instantaneous. We predict the degree of excitation and the range of nuclei reached by neutron evaporation. These findings are relevant for planning future experiments.
CRIS-Team Scopus Importer:2021-05-21

Multiphonon quantum dynamics in cavity optomechanical systems - Macovei, Mihai; Palffy-Buß, Adriana (Physical Review A, 2022)
The multiphonon quantum dynamics in laser-pumped cavity optomechanical samples containing a vibrating mirror is investigated. Especially, we focus on dispersive interaction regimes where the externally applied coherent field frequency detuning from the optical resonator frequency is not equal to the mirror's oscillating frequency or to its multiples. As a result, for moderately strong couplings among the involved subsystems, the quantum dynamics of this complex system is described by multiphonon absorption or emission processes, respectively. Particularly, we demonstrate efficient ways to monitor the phonon quantum dynamics via photon detection. The possibility to extract the relevant sample parameters, for instance, the coupling strength between the mechanical mirror and the electromagnetic field, is also discussed.
CRIS-Team Scopus Importer:2022-03-25

Nuclear clocks for testing fundamental physics - Peik, E.; Schumm, T.; Safronova, M. S.; Pálffy, Adriana; Weitenberg, J.; Thirolf, P. G. (Quantum Science and Technology, 2021)
The low-energy, long-lived isomer in 229Th, first studied in the 1970s as an exotic feature in nuclear physics, continues to inspire a multidisciplinary community of physicists. It has stimulated innovative ideas and studies that expand the understanding of atomic and nuclear structure of heavy elements and of the interaction of nuclei with bound electrons and coherent light. Using the nuclear resonance frequency, determined by the strong and electromagnetic interactions inside the nucleus, it is possible to build a highly precise nuclear clock that will be fundamentally different from all other atomic clocks based on resonant frequencies of the electron shell. The nuclear clock will open opportunities for highly sensitive tests of fundamental principles of physics, particularly in searches for violations of Einstein's equivalence principle and for new particles and interactions beyond the standard model. It has been proposed to use the nuclear clock to search for variations of the electromagnetic and strong coupling constants and for dark matter searches. The 229Th nuclear optical clock still represents a major challenge in view of the tremendous gap of nearly 17 orders of magnitude between the present uncertainty in the nuclear transition frequency (about 0.2 eV, corresponding to ∼48 THz) and the natural linewidth (in the mHz range). Significant experimental progress has been achieved in recent years, which will be briefly reviewed. Moreover, a research strategy will be outlined to consolidate our present knowledge about essential 229mTh properties, to determine the nuclear transition frequency with laser spectroscopic precision, realize different types of nuclear clocks and apply them in precision frequency comparisons with optical atomic clocks to test fundamental physics. Two avenues will be discussed: laser-cooled trapped 229Th ions that allow experiments with complete control on the nucleus-electron interaction and minimal systematic frequency shifts, and Th-doped solids enabling experiments at high particle number and in different electronic environments.
CRIS-Team Scopus Importer:2021-05-14
Keywords: dark matter searches; fundamental physics; nuclear clock; thorium-229 isomer

Nuclear coherent population transfer to the Th 229m isomer using X-ray pulses - Kirschbaum, Tobias; Minkov, Nikolay; Pálffy, Adriana (Physical Review C - Nuclear Physics, 2022)
Population of the 8 eV Th229m isomer via the second nuclear excited state at 29.19 keV by means of coherent X-ray pulses is investigated theoretically. We focus on two nuclear coherent population transfer schemes using partially overlapping X-ray pulses known from quantum optics: Stimulated Raman adiabatic passage, and successive π pulses. Numerical results are presented for three possible experimental setups. Our results identify the Gamma Factory as the most promising scenario, where two ultraviolet pulses combined with relativistically accelerated ions deliver the required intensities for efficient isomer population. Our simulations require knowledge of the in-band and cross-band nuclear transition probabilities. We give theoretically predicted values for the latter and discuss them in the context of recent experiments.
CRIS-Team Scopus Importer:2022-07-22

Physics Opportunities with the Gamma Factory - Budker, Dmitry; Gorchtein, Mikhail; Krasny, Mieczyslaw Witold; Pálffy, Adriana; Surzhykov, Andrey (Annalen Der Physik, 2022)
CRIS-Team Scopus Importer:2022-03-18

Superradiance and anomalous hyperfine splitting in inhomogeneous ensembles - Andrejic, Petar; Pálffy, Adriana (Physical Review A, 2021)
Collective effects in the interaction of light with ensembles of identical scatterers play an important role in many fields of physics. However, often the term "identical" is not accurate due to the presence of hyperfine fields which induce inhomogeneous transition shifts and splittings. Here we develop a formalism based on the Green's-function method to model the linear response of such inhomogeneous ensembles in one-dimensional waveguides. We obtain a compact formula for the collective spectrum, which exhibits deviations from the uniform frequency shift and broadening expected of two-level systems. In particular, if the coherent contribution to the collective coupling is large, the effect of inhomogeneous broadening can be suppressed, with the linewidth approaching that of the superradiant value. We apply this formalism to describe collective effects in x-ray scattering off thin-film waveguides for inhomogeneous hyperfine parameters.
CRIS-Team WoS Importer:2021-09-17

Th 229m isomer from a nuclear model perspective - Minkov, Nikolay; Palffy-Buß, Adriana (Physical Review C - Nuclear Physics, 2021)
The physical conditions for the emergence of the extremely low-lying nuclear isomer Th229m at approximately 8 eV are investigated in the framework of our recently proposed nuclear structure model. Our theoretical approach explains the Th229m-isomer phenomenon as the result of a very fine interplay between collective quadrupole-octupole and single-particle dynamics in the nucleus. We find that the isomeric state can only appear in a rather limited model space of quadrupole-octupole deformations in the single-particle potential, with the octupole deformation being of a crucial importance for its formation. Within this deformation space the model-described quantities exhibit a rather smooth behavior close to the line of isomer-ground-state quasidegeneracy determined by the crossing of the corresponding single-particle orbitals. Our comprehensive analysis confirms the previous model predictions for reduced transition probabilities and the isomer magnetic moment, while showing a possibility for limited variation in the ground-state magnetic moment theoretical value. These findings prove the reliability of the model and suggest that the same dynamical mechanism could manifest in other actinide nuclei giving a general prescription for the search and exploration of similar isomer phenomena.
CRIS-Team Scopus Importer:2021-02-05

Transient nuclear inversion by x-ray free electron laser in a tapered x-ray waveguide - Chen, Yu-Hsueh; Lin, Po-Han; Wang, Guan-Ying; Pálffy, Adriana; Liao, Wen-Te (Physical Review Research, 2022)
The enhancement of x-ray-matter interaction by guiding and focusing radiation from x-ray free electron lasers is investigated theoretically. We show that elliptical waveguides using a cladding material with a high atomic number, such as platinum, can maintain an x-ray intensity of up to three orders of magnitude larger than in free space. This feature can be used to place a nuclear sample in the waveguide focal area and drive nuclear Mossbauer transitions up to transient nuclear population inversion. The latter is a long-standing goal related to gamma-ray lasers or nuclear state population control for energy storage. We show that inverted nuclei numbers of up to approximately 2 x 10(5) are achievable in the realistic region of longitudinal x-ray-free-electron-laser coherence time <= 10 fs. Our results anticipate the important role of tapered x-ray waveguides and strategically embedded samples in the field of x-ray quantum optics.
CRIS-Team WoS Importer:2022-08-05